Cultural Bias in the Perception of Foreign-Policy Events - Felix S. Bethke (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2016)
Cultural bias means individuals judge and interpret a phenomenon according to values that are inherent in their own culture. The same event may be perceived differently by individuals with different cultural backgrounds. This study systematically tests for the presence of cultural differences in the perception of foreign policy events. Using a web survey with a split-sample of Chinese and US foreign policy experts, four domains of foreign policy are explored: sanctions; border violations; foreign aid; and trade agreements. The findings indicate general agreement between Chinese and US experts in the classification of foreign-policy events as cooperative, neutral, or conflictive. In regard to more specific foreign-policy scenarios, the picture is more differentiated. In the case of economic sanctions and border violations, there appears, again, to be general agreement as to the degree of conflictiveness of these events. In addition, perception does not appear to be influenced by collective self-esteem, in the sense that responses remain similar whether the event is described in abstract or country-specific terms. In the case of trade agreements and foreign aid, by contrast, there is a divergence in Chinese and US perceptions in regard to contextual factors such as conditionality and enforcement. Overall, the study suggests that while culture rarely affects the general perception of foreign-policy events, it does play a role in the perception of more complex concepts, such as conditionality and enforcement, that structure the context and meaning of those events.
urn:nbn:de:hbz:464-20160725-081608-9
Keywords: 320; Cultural bias; international cooperation; international conflict; foreign policy; event perception